2020
DOI: 10.3724/sp.j.1042.2020.00904
|View full text |Cite
|
Sign up to set email alerts
|

Workplace status: The multifaceted characteristics and dynamic influence mechanism

Abstract: Exploring the role of emotions in injustice perceptions and retaliation. Journal of Applied Psychology, 90(4), 629-643. Barkow, J. H. (1989). The elastic between genes and culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Chen and Lin (2019) [79] showed that group identity had a positive effect in this study. Liu, Zou and Shu (2019) [78] argue that the organizational identity of employees has a dual impact on the innovative behavior of enterprises. Innovation not only drives innovation through dissatisfaction with the status quo, but also hinders innovation through contentment with the status quo.…”
Section: Research On Organizational Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and Lin (2019) [79] showed that group identity had a positive effect in this study. Liu, Zou and Shu (2019) [78] argue that the organizational identity of employees has a dual impact on the innovative behavior of enterprises. Innovation not only drives innovation through dissatisfaction with the status quo, but also hinders innovation through contentment with the status quo.…”
Section: Research On Organizational Identitymentioning
confidence: 99%
“…In such a company, both individual self-esteem and positive self-awareness are enhanced. Wang, Gao and Shu (2020) [78] wrote that employees have two motivations in the process of maintaining high selfesteem and positive self-concept: the motivation to reduce identity uncertainty and the motivation to improve status. On the one hand, the implementation of social responsibility oriented human resource management practice by enterprises will enable employees to develop high self-esteem and positive self-concept.…”
Section: Research Assumptions the Impact Of Social Responsibility Ori...mentioning
confidence: 99%